Biogeographical characterization of Saccharomyces cerevisiae wine yeast by molecular methods - Tofalo, Rosanna; Perpetuini, Giorgia; Schirone, Maria; Fasoli, Giuseppe; Aguzzi, Irene; Corsetti, Aldo; Suzzi, Giovanna (Frontiers in Microbiology, 2013)
Biogeography is the descriptive and explanatory study of spatial patterns and processes involved in the distribution of biodiversity. Without biogeography, it would be difficult to study the diversity of microorganisms because there would be no way to visualize patterns in variation. Saccharomyces cerevisiae, “the wine yeast,” is the most important species involved in alcoholic fermentation, and in vineyard ecosystems, it follows the principle of “everything is everywhere.” Agricultural practices such as farming (organic versus conventional) and floor management systems have selected different populations within this species that are phylogenetically distinct. In fact, recent ecological and geographic studies highlighted that unique strains are associated with particular grape varieties in specific geographical locations. These studies also highlighted that significant diversity and regional character, or ‘terroir,’ have been introduced into the winemaking process via this association. This diversity of wild strains preserves typicity, the high quality, and the unique flavor of wines. Recently, different molecular methods were developed to study population dynamics of S. cerevisiae strains in both vineyards and wineries. In this review, we will provide an update on the current molecular methods used to reveal the geographical distribution of S. cerevisiae wine yeast.